Interobserver variability in diagnosis of uterine high-grade endometrioid carcinoma - Thomas, Sumi (Arch Pathol Lab Med, 2016)
CONTEXT: Low interobserver diagnostic agreement exists among high-grade endometrial carcinomas. OBJECTIVE: Evaluate diagnostic variability in FIGO grade 3 endometrioid adenocarcinoma (G3EC) in two different sign-out practices. DESIGN: Sixty-six G3EC cases were identified from pathology archives of Wayne State University, Detroit, MI (WSU) (general surgical pathology sign-out) and 65 from Memorial Sloan Kettering Cancer Center, New york, NY (MSK) (gynecologic pathology focused sign-out). Each case was reviewed together by two gynecologic pathologists, one from each institution, and classified into G3EC group or reclassified group. Clinicopathological parameters were compared. RESULTS: Twenty-five (38%) WSU cases were reclassified as undifferentiated (2), serous (4), mixed endometrioid and serous (12) carcinomas, and FIGO grade 2 endometrioid (G2EC) with focal marked nuclear atypia (7). Eleven (17 %) MSK cases were reclassified as undifferentiated (5), serous (1), mixed endometrioid and serous (4), mixed endometrioid and clear cell (1) carcinomas. Agreement rate between original and review diagnosis was 83% (54 of 65) at MSK and 62% (41 of 66) at WSU (P= .01) with overall rate of 73% (95 of 131). Undifferentiated carcinomas were higher at MSK than WSU (46 %, 5 of 11 vs. 8%, 2 of 25; P= .02). G2EC with focal marked nuclear atypia was higher in WSU (28%, 7 of 25) than MSK (0%) (P= .03). Mixed endometrioid and serous carcinoma was the most common misclassified subtype (44%, 16 of 36). CONCLUSIONS: Moderate interobserver variability exists in the diagnosis of G3EC with significantly higher diagnostic agreement rate in gynecologic pathology focused sign-out than general sign-out practice.